Solvent control of charge transfer excited state relaxation pathways in [Fe(2, 2′-bipyridine)(CN)4]2−. Issue 6 (24th January 2018) - Kjær, Kasper S.; Kunnus, Kristjan; Harlang, Tobias C. B.; Van Driel, Tim B.; Ledbetter, Kathryn; Hartsock, Robert W.; Reinhard, Marco E.; Koroidov, Sergey; Li, Lin; Laursen, Mads G.; Biasin, Elisa; Hansen, Frederik B.; et al.
Abstract : By combining transient X-ray and optical studies, we reveal the solvent influence on excited state potential energy surfaces of [Fe(bpy)(CN)4 ] 2− . Abstract : The excited state dynamics of solvated [Fe(bpy)(CN)4 ] 2−, where bpy = 2, 2′-bipyridine, show significant sensitivity to the solvent Lewis acidity. Using a combination of optical absorption and X-ray emission transient spectroscopies, we have previously shown that the metal to ligand charge transfer (MLCT) excited state of [Fe(bpy)(CN)4 ] 2− has a 19 picosecond lifetime and no discernable contribution from metal centered (MC) states in weak Lewis acid solvents, such as dimethyl sulfoxide and acetonitrile. 1, 2 In the present work, we use the same combination of spectroscopic techniques to measure the MLCT excited state relaxation dynamics of [Fe(bpy)(CN)4 ] 2− in water, a strong Lewis acid solvent. The charge-transfer excited state is now found to decay in less than 100 femtoseconds, forming a quasi-stable metal centered excited state with a 13 picosecond lifetime. We find that this MC excited state has triplet ( 3 MC) character, unlike other reported six-coordinate Fe(ii )-centered coordination compounds, which form MC quintet ( 5 MC) states. The solvent dependent changes in excited state non-radiative relaxation for [Fe(bpy)(CN)4 ] 2− allows us to infer the influence of the solvent on the electronic structure of the complex. Furthermore, the robust characterization of the dynamics and optical spectral signatures of the isolated 3 MC intermediate provides a strong foundation for identifying 3 MC intermediates in the electronic excited state relaxation mechanisms of similar Fe-centered systems being developed for solar applications.